2019
DOI: 10.1001/jamapsychiatry.2018.3126
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Opioid Misuse and Addiction

Abstract: ore than 2 million Americans have an opioid use disorder (OUD), and in 2016, more than 42 000 Americans died of opioid overdoses. 1,2 Although in the first years of the opioid crisis, most overdose-associated deaths were caused by misuse of prescription analgesics, heroin and synthetic opioids (fentanyl and its analogues) currently account for most of the fatalities, a scenario that reflects the changing nature of the opioid crisis (Figure 1). We reviewed the pharmacology of opioids because it is relevant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
330
0
12

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 447 publications
(386 citation statements)
references
References 58 publications
(78 reference statements)
5
330
0
12
Order By: Relevance
“…Of particular note is the opioid crisis in the U.S., where drug overdoses involving opioids resulted in more than 400,000 deaths during the last two decades as a consequence of this opioid epidemic [13,14]. Further, the evidence regarding chronic opioid therapy (COT) (opioid therapy > 90 days) for chronic pain [6,15,16] is increasingly highlighting the risks, e.g., opioid hyperalgesia, opioid use disorder, and loss of beneficial effects over time [7,[17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note is the opioid crisis in the U.S., where drug overdoses involving opioids resulted in more than 400,000 deaths during the last two decades as a consequence of this opioid epidemic [13,14]. Further, the evidence regarding chronic opioid therapy (COT) (opioid therapy > 90 days) for chronic pain [6,15,16] is increasingly highlighting the risks, e.g., opioid hyperalgesia, opioid use disorder, and loss of beneficial effects over time [7,[17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Research from the United States, Australia, Canada, and European countries have shown a significant increase in opioid utilization during the past decade to such a scale that several countries (United States, Canada, Australia) have called for an organized response to the opioid crisis . In 2017, the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) reports that while some parallels exist, the overall European situation remains different to that reported from the United States .…”
Section: Introductionmentioning
confidence: 99%
“…The abuse of prescription and recreational opioids has culminated in a growing national healthcare crisis, with substantial efforts being devoted to the development of novel pharmacotherapeutics that can safely and more effectively reduce opioid misuse and dependence as compared to currently-available medications (Blanco and Volkow 2019;Kreek et al 2019;Volkow et al 2019). It is well-established that the abuse-related effects of opioids are mediated largely via their capacity to increase dopamine (DA) neurotransmission within the mesolimbic reward system (for review, see Di Chiara and North 1992;McBride et al 1999;Pierce and Kumaresan 2006;Reiner et al 2019;Wise 1989), a projection that arises from DAergic cells located in the ventral tegmental area (VTA) and terminates in the nucleus accumbens (NAc) (Bjorklund and Dunnett 2007;Moore and Bloom 1978).…”
Section: Introductionmentioning
confidence: 99%